Developing and Implementing a Flexible Web-based Teaching/Learning Environment Across an Entire Academic Organisational Unit : Final Report for a 1997 National Teaching Development Grant (Organisational). - Hedberg, John; Harper, Barry; Patterson, John; Subic, Aleksander; Coban, Turhan; Bushnell, Gerald (Committee for University Teaching and Staff Development (CUTSD), 1997)
Final report of a National Teaching Development Grant at the University of Wollongong. The project was originally conceived to build on the work of the Information Technology in Education Strengths of the Graduate School of Education which had produced three award winning CD-ROM products. Some subjects had been experimenting with online delivery through independent initiatives. The project worked with all staff teaching in the postgraduate program to convert some or all of their content into a form where it was supported by a website and resources which were richer and not purely dependent on traditional distance or classroom-based learning activities. As part of this project, a series of online resources and performance support systems were developed to assist with the evaluation and implementation of technology-based learning. These formed the basis for early developments. The project sought to specifically address the potential loss of students in a time where they were being asked to pay full-fees for their postgraduate education.